Evaluation of 3D Printing of Cereal–Legume Starch-Based Gels Formulated with Red Adzuki Bean and Germinated Brown Rice Flour - Ran Liu; Yu Zhuang; Jiakai Song; Liuyang Shen; Yanling Yin (Foods)
Three-dimensional (3D) food printing (3DFP) is an emerging technology that enables the creation of personalized and functional foods by precisely controlling nutritional content and shape. This study investigated the 3D printability and rheological behavior of cereal–legume starch-based gels formulated with germinated brown rice (GBR) and red adzuki bean (RAB) flours, supplemented with xanthan and guar gums as functional additives. The physicochemical and structural properties of the gels were characterized through FT-IR, rheology, texture analysis, SEM, and sensory evaluation. In addition, the 3D printing fidelity, rheological behavior, color attributes, textural properties, microstructure, and sensory scoring of the printed products were evaluated. The results indicated that the gels exhibited pseudoplastic behavior, with the RABF/GBRF ratio of 1:2 (RG1:2) formulation showing optimal color properties (ΔE* = 0.60 ± 0.86) and the RABF/GBRF ratio of 2:1 (RG2:1) formulation demonstrating superior printing fidelity and structural stability (printing accuracy = 99.37 ± 0.39%). The gels’ mechanical properties, such as hardness and chewiness, were significantly influenced by the RABF and GBRF ratios, with RG2:1 exhibiting the highest hardness (1066.74 ± 102.09) and RG1:2 showing the best springiness (0.64 ± 0.10). The sensory evaluation results indicated that the RABF/GBRF ratios of 1:1 (RG1:1) and RG1:2 had relatively high overall acceptance scores. These findings indicate that specific ratios of RABF and GBRF improve the 3D printability and textural properties of cereal–legume starch-based gels, enhancing their suitability for 3D food printing applications. This study provides valuable insights into the development of personalized and functional cereal–legume starch-based foods using 3DFP technology.